The Influence of Price, Product Quality, and Promotion on Purchasing Decisions for ABC Sambal Sauce Products (Study of consumers in the city of Surabaya) - Solith Paschal Silaban; Ety Dwi Susanti (Lavish Opulent Education, 2026)
This study examines the influence of price, product quality, and promotion on purchasing decisions of ABC chili sauce among consumers in Surabaya. The background of this research is the increasingly intense competition in the food and beverage industry, particularly in the chili sauce market, which has led to changes in consumer preferences and a decline in the Top Brand Index of ABC chili sauce in recent years. Therefore, it is important to understand the factors that influence consumer purchasing decisions. The purpose of this study is to analyze the effect of price, product quality, and promotion on purchasing decisions both simultaneously and partially. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to consumers who have purchased or consumed ABC chili sauce in Surabaya. The sampling technique used was non-probability sampling with a total of respondents determined according to research criteria. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing including the F test and t test. The results of the study indicate that price, product quality, and promotion simultaneously have a significant influence on purchasing decisions. Partially, each variable—price, product quality, and promotion—also shows a positive and significant effect on consumer purchasing decisions. These findings suggest that consumers tend to consider affordable prices, good product quality, and attractive promotional strategies when deciding to purchase ABC chili sauce. In conclusion, the combination of competitive pricing, consistent product quality, and effective promotional activities plays an important role in influencing consumer purchasing decisions. The implication of this study is that companies should continuously improve product quality, maintain competitive pricing strategies, and develop more effective promotional activities in order to strengthen their market position and increase consumer purchasing decisions.